G2-S16 dendrimer microbicide does not interfere with the vaginal immune system - Alba Martín-Moreno (Journal of Nanobiotechnology, 2019)
Abstract It is essential that prophylactic drugs do not interfere with the normal function of the immune system. The use of nanoparticles as vaginal microbicides is a promising prevention strategy against sexually transmitted infections. With that aim, our group is working with the G2-S16, a second generation carbosilane dendrimer with sulfonate groups in the periphery, which has been previously shown to be effective against HIV-1 and HSV-2 infection, and it is now on the road to clinical trials. Our objective in this new study is to assess the effects of G2-S16 on the immune barrier of the female reproductive tract. The expression of differentiation, maturation and activation markers was measured in epithelial cells, dendritic cells, M and GM macrophages, and T cells using RT-qPCR and flow cytometry. The results demonstrate that G2-S16 does not alter the natural immunity of the vagina, strongly supporting the biosafety of this dendrimer for clinical use.